Development of a 3D human digital twin with soft-body feet for human-robot interaction simulation - Loke, Kum Yew (Nanyang Technological University, 2024)
With the increasing use of assistive robots in rehabilitation and assisted mobility of human patients, there has been a need for a deeper understanding of human-robot interactions. One of the key solutions to this is human-robot interaction simulations, which provide an understanding to these interactions in a digital environment. Hence, there has been ongoing work in the development of such simulations. More specifically, there has been an emphasis on the accurate modelling of humans in such simulations, to glean more accurate results and better insights on human-robot interactions. This report details the development of a 3D human digital twin model with soft-body feet for human-robot interaction simulation. The work in this report builds upon an ongoing work at the Rehabilitation Research Institute of Singapore in developing a Human-In-The-Loop robotics simulation, and primarily aims to add soft tissue simulation capabilities to the human body model.